Beyond Bilingual Education: Multilingual Language Education in Nepal - Taylor, Shelley K. (GIST – Education and Learning Research Journal, 2010)
the purpose of this paper is to describe the framework for implementing multilingual language education (MLE) countrywide in Nepal. I outline key tenets of MLE, explain the rationale for implementing it in the Nepali context, and describe the MLE framework that formed the basis of trainer workshops. The framework is divided into 7 topics: 4 of which are specific to MLE, and therefore not discussed in this paper. I argue that MLE should be implemented in other countries for both educational and socio-political reasons relating to the educational well-being of lingusitic minority children.